CUSTOMER ORIENTATION IN THE MARKETING ACTIVITY OF ROMANIAN COMPANIES - Andreea-Daniela, MORARU; Cristina, DUHNEA (Strategii Manageriale)
Market orientation is used to describe the actual implementation of the marketing concept or in other words induces the idea that organizations which are market-oriented act according to the marketing principles. The scope of this article is therefore to nvestigate and empirically assess the perceived impact of customer orientation as main component of market orientation on business performance using a sample of Romanian companies. The research results reveal the importance of this dimension and of the items used to assess customer orientation on business performance and represents a starting point for further research in the field.